2018
DOI: 10.1073/pnas.1720177115
|View full text |Cite
|
Sign up to set email alerts
|

Material barriers to diffusive and stochastic transport

Abstract: SignificanceObservations of tracer transport in fluids generally reveal highly complex patterns shaped by an intricate network of transport barriers and enhancers. The elements of this network appear to be universal for small diffusivities, independent of the tracer and its initial distribution. Here, we develop a mathematical theory for weakly diffusive tracers to predict transport barriers and enhancers solely from the flow velocity, without reliance on diffusive or stochastic simulations. Our results yield … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 37 publications
8
107
0
Order By: Relevance
“…They are well documented in geophysics [33], classical fluid dynamics [23], plasma fusion [6], reactive flows [27] and molecular dynamics [32], yet no general theory for them has been available until recently. In [13], we have put forward such a theory for incompressible flows and weakly diffusing substances by defining and solving an extremum problem for material surfaces that block the diffusive transport of passive scalars more than neighboring surfaces do.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are well documented in geophysics [33], classical fluid dynamics [23], plasma fusion [6], reactive flows [27] and molecular dynamics [32], yet no general theory for them has been available until recently. In [13], we have put forward such a theory for incompressible flows and weakly diffusing substances by defining and solving an extremum problem for material surfaces that block the diffusive transport of passive scalars more than neighboring surfaces do.…”
Section: Introductionmentioning
confidence: 99%
“…While valid in arbitrary dimension, the results in [13] rely explicitly on the assumption that the flow carrying the concentration field of interest is incompressible. Fluid flows arising in applications are indeed practically incompressible, but air flows are relatively easy to compress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These velocities are derived from satellite altimetry data. We choose a time window (starting November 26, 2016) for which a small spatial piece has been used repeatedly as a data set "benchmark" case in the literature; cf., for instance, [24,14], and earlier studies on slightly larger domains [23,29]. The domain studied in the first references is highlighted by a small white rectangle in Figs.…”
Section: Global Ocean Surface Flowmentioning
confidence: 94%
“…In this framework, material barriers to diffusive and stochastic transport have been defined in [24] as material surfaces which extremize diffusive transport over the finite observation time interval. There, it is shown that in two-dimensional flows, the diffusive transport through a one-dimensional material manifold Γ is given in leading order (with respect to diffusivity ε) by…”
Section: Mathematical Settingmentioning
confidence: 99%